Does differentiation strategy model matter? Designation of organizational performance using differentiation strategy instruments: An empirical analysis - Xhavit Islami; Marija Topuzovska Latkovikj; Ljubomir Drakulevski; Mirjana Borota Popovska (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Considering pursuing the differentiation strategy makes enable the organization to earn its success and to create, capture and sustain economic value. Despite this importance, it is relatively absentminded in empirical studies at the conceptual level. In response to this gap, the purpose of this paper is conceptualizing differentiation strategy model, developing the instruments of differentiation strategy, and testing the relationship between dimensions of the value chain, differentiation in the supply, competitive advantages, and organizational performance, using data from a sample of 123 manufacturing organizations. On this study, quantitative methods were applied to measure the proposed relationships, and questionnaires were used as a tool in gathering primary data. Relationships proposed in the framework were tested using structural equation modeling. The results of this study indicated that pursuing the differentiation strategy leads on increasing competitive advantage and improving organizational performance. Also, it pointed out that the manufacture organizations' success is determined by their ability to be flexible on strategic planning and on integrating internal and industrial settings factors on differentiation strategy creating. This research contributes to strategic literature clarifying a successful differentiation model helping the practitioners on increasing the ability and knowledge on pursuing the differentiation strategy.
Keywords: L1; O21; O14; M21; L22; 650; differentiation strategy; business model; distinctive value chain; competitive advantage; organizational performance